Angels - Peter Lamborn Wilson (USA Pantheon Books, 1980)
A collection of paintings, drawings and sculpture of angels
Prelude. The kabbalist ; The philosopher ; The shaman -- The image of the Angel -- Angel's work. Definitions ; The angel of the Lord ; The Logos ; Sophia ; The archangels and Satan ; Dwellers in paradise ; The nature of Heaven ; Space and time ; Death and love ; Angelic eroticism ; The Muse ; The Guardian Angel -- Journeys. The ladder ; Black Elk ; To ascend, to escape ; Orient and Hyperborea ; The miraculous night journey ; Visionary recitals ; The Grail cycle ; Trickster invades Heaven ; Dionysius and the Paradiso -- Ritual and mysticism. Angelic rites ; Calling down the angel ; Becoming an angel
Prelude. The kabbalist ; The philosopher ; The shaman -- The image of the Angel -- Angel's work. Definitions ; The angel of the Lord ; The Logos ; Sophia ; The archangels and Satan ; Dwellers in paradise ; The nature of Heaven ; Space and time ; Death and love ; Angelic eroticism ; The Muse ; The Guardian Angel -- Journeys. The ladder ; Black Elk ; To ascend, to escape ; Orient and Hyperborea ; The miraculous night journey ; Visionary recitals ; The Grail cycle ; Trickster invades Heaven ; Dionysius and the Paradiso -- Ritual and mysticism. Angelic rites ; Calling down the angel ; Becoming an angel
Keywords: Biblical Studies (3ebOeGJ hOQGSGJ GdcJGH GdebOSs; Bible; Angels in art; Art and religion